Severe leptospirosis with acute kidney injury: a case description and literature review : case reports - Daschner, Clara; Schübler, Anna-Sophie; Jung, Matthias; Ayasse, Niklas; Yücel, Gökhan; Husain-Syed, Faeq; Leipe, Jan; Krämer, Bernhard; Yazdani, Babak (Nephron, 2024)
Introduction: Leptospirosis is a globally transmitted zoonotic disease caused by Leptospira spp., a highly mobile, obligate aerobic, spiral-shaped bacteria. Described first by Adolf Weil in 1886, leptospirosis in Germany is rare, leading to a delayed diagnosis due to diverse symptoms. Most cases are mild, but severe forms, like Weil’s disease, cause life-threatening complications such as fever, jaundice, hemoptysis, and acute kidney injury (AKI). The aim of this work was to provide a literature review of leptospirosis with renal manifestation based on a case report. Case Presentation: We report the case of an 81-year-old male patient with initially unclear oliguric AKI, bilateral pulmonary infiltrates, and jaundice. After excluding common AKI causes, the expanded patient history suggested possible rat contact in his chicken coop. Finally, we serologically identified an infection with Leptospira spp. by positive IgM, proving that the illness was compatible with classical Weil’s disease. The patient underwent temporary hemodialysis and antibiotic treatment with intravenous penicillin G for 2 weeks. Under therapy, the AKI, hyperbilirubinemia, and clinical condition of the patient improved. The patient was discharged after 2 weeks. In the following controls, slightly impaired kidney function was observed, indicating a progress of his chronic kidney disease (CKD). Conclusion: Although leptospirosis is rare, there are some cases with a fulminant course. Impairment of renal function often correlates with severity of the disease requiring antibiotic treatment. In some cases, AKI progresses to CKD demonstrating the need to raise awareness for leptospirosis.
Online veröffentlicht: 5. August 2024
Gesehen am 07.04.2025